2011
DOI: 10.1186/1472-6963-11-233
|View full text |Cite
|
Sign up to set email alerts
|

A theory-based educational intervention targeting nurses' attitudes and knowledge concerning cancer-related pain management: A study protocol of a quasi-experimental design

Abstract: BackgroundPain is one of the most frequent problems among patients diagnosed with cancer. Despite the availability of effective pharmacological treatments, this group of patients often receives less than optimal treatment. Research into nurses' pain management highlights certain factors, such as lack of knowledge and attitudes and inadequate procedures for systematic pain assessment, as common barriers to effective pain management. However, educational interventions targeting nurses' pain management have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Drawing on previous studies, Borglin, Gustafsson and Krona [14] describe using the Theory of Planned Behaviour to develop a series of workshops for nurses to improve pain management for cancer patients. The Normalisation Process Model [15] was used as a theoretical framework in two RCTs in maternity care and was reported to be of value in understanding organisational contexts into which new models of care are introduced [16].…”
Section: Resultsmentioning
confidence: 99%
“…Drawing on previous studies, Borglin, Gustafsson and Krona [14] describe using the Theory of Planned Behaviour to develop a series of workshops for nurses to improve pain management for cancer patients. The Normalisation Process Model [15] was used as a theoretical framework in two RCTs in maternity care and was reported to be of value in understanding organisational contexts into which new models of care are introduced [16].…”
Section: Resultsmentioning
confidence: 99%
“…Modern programs have been implemented in Australia, the USA, and Sweden, suggesting that there is considerable room for local improvement. [ 36 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nurse stated 'Patients don't really know how to rate pain, some always rate the pain the same, but they are able to sleep' [10]. Borglin et al [34] argue that patients perceived the crucial role in increasing pain levels is that having their pain assessed incorrectly. The study was also consistent with Fothergill-Bourbonnais and Wilson-Barnett [28] who concluded that clinical experience is the most influential factor that promotes nurses knowledge and confidence in managing patient's pain.…”
Section: Discussionmentioning
confidence: 99%
“…The non-oncology nurses showed more confidence than oncology nurses in using aspirin and using analgesics in patients with acute abdomen (q 23 and 24). However, the most significant barrier to undertaking an effective pain management is nurses' reliance on their own subjective judgment [10,34]. To manage patient pain effectively, nurses must trust patient self-report, even if it appears incongruent with the patient's nonverbal behavior or the nurses' individual beliefs.…”
Section: Discussionmentioning
confidence: 99%